30- day outcome after orthopaedic surgery in patients assessed as negative for COVID-19 at the time of surgery during the peak of the pandemic. (2020) - Price, A.; Shearman, A. D.; Hamilton, T. W.; Alvand, A.; Kendrick, B.
No abstract available